Relationship between root and shoot growth traits during the plant crop and first ratoon in banana and plantain (Musa spp.) and its implications for perennial cultivation on degraded Ultisols in southeastern Nigeria. - Blomme, Guy; Swennen, Rony L.; Soka, G.; Turyagyenda, L.F.; Tenkouano, A. (2008)
The effect of cycle on root system and shoot development was studied for two crop cycles (plant crop and first ratoon). The study revealed that shoot and root system development declined from the plant crop to the first ratoon for plants grown on degraded Ultisols in south-eastern Nigeria.